Gestão de múltiplos projetos em uma empresa de bens de capital: uso do método da corrente crítica aplicando lógica fuzzy para cálculo de pulmão de tempo - Campanini, Luciano (Universidade Federal de São Carlos, 2013)
This study approach the Critical Chain Method. This method is the Theory of Constraints applied to project management. The main contribution of this thesis is to propose a method for determining buffer size. Some literature reviews were performed on research methodology, production systems, project management, Critical Chain and Fuzzy Logic. A case study in a multiple project environment in a company that works with engineering to orders in the segment of capital goods was done. At the literature for determining buffer size, were identified in addition to the original method "Cut and Paste Method" proposed by Goldratt, four other methods: "Root Square Error Method (RSEM)", "Adaptive Procedure with Density (APD)," Adaptive Procedure with Resource Tightness (APRT) "and" Improved Root Square Error Method (IRSEM)". In the literature considered in this work, there was no application of any of the Critical Chain method in cases of multiple projects, with these four methods for determining buffer size. For the proposal of a new method for determining buffer size, elaborated in this thesis, we considered five variables that influence the outcome of the contracts and thus integrate the formulation. They are: contractual penalty, profit margin, customer importance, project complexity and resource constraints. Fuzzy logic is used to establish an adjustment factor to determining the buffer size. All these methods were simulated in the environment of multiple projects studied and some indicators were compared. In general, the proposed of buffer size using Fuzzy Logic allows the use of a greater number of project specific characteristics to determining the buffer size and the results of applications were goods when compared with other buffer size methods considered in this literature.
Keywords: Gerenciamento de projetos industriais; Corrente crítica; Fuzzy logic; Múltiplos projetos; Pulmão de tempo; Critical chain; Project management; Multi-projects; Buffer size; ENGENHARIAS::ENGENHARIA DE PRODUCAO